Prevalence of Bovine Trypanosomosis and Its Associated Risk Factor in Hawa Galan District, Kelem Wollega Zone of Ethiopia - Girma Tsegaye; Belay Abebe; Geremew Haile (Veterinary Medicine International)
An analytical cross-sectional study was performed between November 2015 and April 2016 at Hawa Galan woreda, Kelem Wollega Zone, Oromia Region, Ethiopia, to estimate the proportion of cattle with trypanosomosis and to evaluate the elements associated with the prevalence of bovine trypanosomosis. A haemoparasitological examination of the Buffy coat method was implemented to determine the proportion of trypanosomosis-positive cattle. A study population of 428 bovines was randomly selected from three peasant associations (PAs) and tested for the presence of the disease. Findings of the laboratory results indicate that among all animals tested at the study time, 26 (6%) animals were positive for the disease. Among the positive results, the proportion of trypanosome species was Trypanosoma congolense 18 (69.3%) and Trypanosoma vivax 8 (30.7%). The prevalence at the selected PAs was 12.5%, 3.8%, and 3% for Lemlem, Madawalkituma, and Ifajiru, respectively. From this finding, the relationship has a statistically significant variation (P < 0.05) among peasant associations and body condition state, and the proportion was significantly greater (P < 0.05) in animals categorized under poor body condition score. The relationships between age and sex of cattle show no statistically significant variation among them (P > 0.05). This study indicates that the proportion of trypanosomosis was greater in anemic (PCV<24%) cattle than nonanemic (PCV≥24%). Therefore, based on this finding, the proportion of bovine trypanosomosis is evident that can cause a major effect on the health of cattle in the study population in the study area. So, effective control methods could be applied to decrease the disease and its related economic loss.